2016
DOI: 10.1007/978-3-319-38855-7_12
|View full text |Cite
|
Sign up to set email alerts
|

Topological Aspects of Irredundant Intersections of Ideals and Valuation Rings

Abstract: An intersection of sets A = i∈I B i is irredundant if no B i can be omitted from this intersection. We develop a topological approach to irredundance by introducing a notion of a spectral representation, a spectral space whose members are sets that intersect to a given set A and whose topology encodes set membership. We define a notion of a minimal representation and show that for such representations, irredundance is a topological property. We apply this approach to intersections of valuation rings and ideals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In particular, Zariski showed that Zar(K|D), endowed with a natural topology, is always a compact space [34, Chapter VI, Theorem 40]; this result has been subsequently improved by showing that Zar(K|D) is a spectral space (in the sense of Hochster [18]), first in the case where K is the quotient field of D [4,5], and then in the general case [8,Corollary 3.6(3)]. The topological aspects of the Zariski space has subsequently been used, for example, in real and rigid algebraic geometry [19,31] and in the study of representation of integral domains as intersections of valuation overrings [26,27,28]. In the latter context, i.e., when K is the quotient field of D, two important properties for subspaces of Zar(K|D) to investigate are the properties of compactness and of Noetherianess.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Zariski showed that Zar(K|D), endowed with a natural topology, is always a compact space [34, Chapter VI, Theorem 40]; this result has been subsequently improved by showing that Zar(K|D) is a spectral space (in the sense of Hochster [18]), first in the case where K is the quotient field of D [4,5], and then in the general case [8,Corollary 3.6(3)]. The topological aspects of the Zariski space has subsequently been used, for example, in real and rigid algebraic geometry [19,31] and in the study of representation of integral domains as intersections of valuation overrings [26,27,28]. In the latter context, i.e., when K is the quotient field of D, two important properties for subspaces of Zar(K|D) to investigate are the properties of compactness and of Noetherianess.…”
Section: Introductionmentioning
confidence: 99%
“…An overring of D is an integral domain contained between D and its quotient field K; the collection of all overrings of D is denoted by Overr(D). Under the Zariski topology, this space is closed in the constructible topology of SMod D (K) (this essentially follows from [36]); in particular, Overr(D) is a spectral space and a subbase for the open sets of Overr(D) is formed by the sets in the form O F := {B ∈ Overr(D) | B ⊇ F }, where F runs among the finite subsets of K.…”
Section: Applicationsmentioning
confidence: 99%
“…As follows in Remark 4.4, properties of the Zariski topology, which are the focus of the next section, can be derived from the patch topology, so our approach in this section is to focus on the patch limit points of subsets of Q * (D) and use this description in the next section to describe properties of the Zariski topology of Q * (D). The patch topology is a common tool for studying the Zariski-Riemann space of valuation rings of a field; see for example [3,4,17,25,26,27,28].…”
Section: The Patch Topology Of Q * (D)mentioning
confidence: 99%